Emosi Dan Tingkahlaku Ibu Tunggal Selepas Perceraian - Faizul, Adenan (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research was done to study and recognize the emotions and behaviors of single mothers after divorce on various aspects such as emotional, behavioral, financial stability and environmental factors which affects the participant of the research. The participant is a single mother who divorced 13 years ago and has children including one who died a few years ago. The researcher used story-based, semi-structured interviews and observation as a method to collect information and data. The information and data are processed by using transcript and analysis of the data provided. The result shows that the participant is happy of the divorce even though she hail to endure a lot of hardship. However, there is enormous pressure on her because of perception of others on her and the lack of support on her either from the community nor her own family. Result shows that single mothers faces high workload risk because of. financial constraints. The emotion and behavior of single mothers also changes in the long-term. All parties in the society must hold responsibilty and take action for the well-being of single mothers.